Improving Logistics Processes Using Lean Management Concept: A Case Study - Natalia PAWLAK; Natalia GIBUS (Communications of International Proceedings, 2024)
Lean Management in logistics is an approach aimed at streamlining processes, increasing efficiency, and reducing waste. The article presents the benefits and challenges of implementing Lean Management in logistics, focusing on methods such as 5S, standardization, and Kaizen. Through a case study of Prime Auto Parts[1] company, specializing in the distribution of automotive parts, the real effects of implementing these methods are shown. The results included a reduction in order picking time, a decrease in errors, increased employee engagement, and the promotion of a culture of continuous improvement. Thanks to Lean Management, Prime Auto Parts company reduced operating costs, improved service quality, and increased customer satisfaction. The article emphasizes that implementing Lean Management in logistics is an investment that brings tangible benefits in both the short and long term.
Keywords: Lean Management; logistics; continuous improvement